2020
DOI: 10.3390/app10155084
|View full text |Cite
|
Sign up to set email alerts
|

Rigenera® Autologous Micrografts in Oral Regeneration: Clinical, Histological, and Radiographical Evaluations

Abstract: Tissue engineering represents a novel approach that aims to exploit the use of biomaterials composed mainly of scaffolds, cells (or grafts), and growth factors capable of restoring a specific tissue. Biomaterials represent the future of dental and oral regeneration due to their biocompatibility and affinity with the receiving site. The aim of this review was to collect results and considerations about a new type of biomaterial based on the use of micrografts in combination with different scaffolds. Micrografts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…Although it has been well demonstrated that CAF + CTG is the gold standard treatment for root coverage procedures [ 6 , 7 , 9 ], patient morbidity, the need for a second surgical site, and limited availability are the main drawbacks of autogenous grafts [ 13 , 14 , 16 ]. Therefore, it is not surprising that several soft-tissue-graft substitutes and biologic agents have been explored in the last two decades for the treatment of gingival recessions [ 18 , 20 , 57 , 58 ]. Among them, platelet concentrates have progressively gained popularity among clinicians due to their properties of enhancing wound healing [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been well demonstrated that CAF + CTG is the gold standard treatment for root coverage procedures [ 6 , 7 , 9 ], patient morbidity, the need for a second surgical site, and limited availability are the main drawbacks of autogenous grafts [ 13 , 14 , 16 ]. Therefore, it is not surprising that several soft-tissue-graft substitutes and biologic agents have been explored in the last two decades for the treatment of gingival recessions [ 18 , 20 , 57 , 58 ]. Among them, platelet concentrates have progressively gained popularity among clinicians due to their properties of enhancing wound healing [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several etiological factors such as tissue phenotype, gingival thickness, brushing technique, non-carious and carious cervical lesions, and periodontal predisposition were identified for this condition [2], which may account for its relatively high incidence in the population (45%) [3][4][5]. Root coverage procedures have been shown to be effective in treating single and multiple GRs [6][7][8], with large evidence supporting the superiority of coronally advanced flap (CAF) combined with connective tissue graft Medicina 2021, 57, 144 2 of 20 (CTG) [9][10][11]. Indeed, CAF + CTG provides the best mean root coverage (mRC) and aesthetic results, compared to alternative procedures such as free gingival graft or tunnel techniques [7,12], with clinical outcomes stable also in the long term [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant micrograft suspension is deposited inside the syringe and used to embed a hydroxyapatite or collagen sponge for 10 min in order to form a biocomplex. 27,36 A specific study conducted by Brunelli and colleagues and carried out at the Oral Surgery Department of the Don Orione hospital in Bergamo, showed that micrografts derived from dental pulp poured onto a collagen sponge are a useful method for bone regeneration in the atrophic jaw. this study was carried out on a 45-year-old male patient, who was rechecked after 4 months using a computed tomography scan and a special computer program to assess bone density.…”
Section: The Use Of Dpscs Through Rigenera Technologymentioning
confidence: 99%
“…Nevertheless, according to Trovato et al, the use of a micrograft (a collagen membrane enriched with stem cells) has potential in the regenerative process [74]. A recent review by Mummolo et al suggested that micrografts in periodontal and bone regeneration are a good alternative to GTR or to other biomaterials such as bone substitutes [75]. However, they have some limitations due to the availability of progenitor cells in the tissue sample used, and the selection of the right scaffold as a carrier.…”
Section: Future Therapiesmentioning
confidence: 99%